Have Digitalization and Credit Access Accelerated Growth Performance in East Java? : A Spatial Econometric and Google Trend Analysis - Ragdad Cani Miranti; Deltha Airuzsh Lubis; Yongky Choirul Anam (East Java Economic Journal, 2023)
This article evaluates the effect of digitalization and credit access in boosting regional growth performance across 38 districts in East Java over the 2010-2021 period. Using google trend analysis, we capture the pattern and spatial distribution of main explanatory variables, which are digitalization and credit access to support our empirical findings. Results show that overall the google trends’ portraits indicate adequate similarities in credit access, which declare the negative yet significant effect to growth. We also find interesting findings to be highlighted for internet access. Both google trends and empirical data show negative correlation between digitalization and credit access. From the standpoint of spatial spills-over effect, there is significant and positive spatial autocorrelation in internet access across districts in Indonesia. Applying spatial econometric model, two key factors appear to boost economic growth in the recovery period, which are digitalization and education-related variable. This article concludes that digitalization can not work itself. The inclusion of spills-over effect and spatial dependence across districts is needed to accelerate regional growth. Thus, from policy perspectives, our findings suggest that spatial-based policies by combining digitalization with human capital are more appropriate to boost growth performance in East Java.